Novel immunotherapy for adult T-cell leukemia/lymphoma: Targeting aurora kinase A - Casey, Nicholas Paul (Oncoimmunology, 2016)
Adult T-cell leukemia/lymphoma is caused by infection with HTLV-1, following a long latent period. Immunotherapy targeting Aurora kinase A, a tumor-associated antigen over-expressed in adult T-cell leukemia/lymphoma, holds great therapeutic potential. We review the evidence in favor of a therapeutic strategy combining vaccination and TCR-gene transfer against this target.